The Relationship between Personal and Environment Factors and Consumer’s Perception on Tent Café in Monas Park, Jakarta - Rini Andriyani; Asep Rustiawan; Lilik Noor Yuliati (Media Gizi dan Keluarga, 2000)
The objective ot this research is to identify the profile and perception of tent café, domain atributes of tent cafe, and the relationship between personal and environment factor with consumer’s perception. This research was conducted in MONAS Park, Jakarta, from September to Oktober 1999. The total samples were 100 consumers from 8 tent cafes. They were chose if they have visited the cafes at least twice. They were interviewed during their visit in the tent café by using questionnaire. Anova and Duncan analysis showed that the domain aspect on tent cafes were pleasure and tasteful. The Spearman analysis showed that price was the important aspect that attract young consumers, while celebrities and entertainment aspect attract high educated consumers. Variety of menu was the considerable aspect that attract the consumers who reach the café in a long distance, while entertainment was meaningful aspect to the old consumers. Tent café were more interested in karaoke than life show or radio and tape recorder.Keywords: consumer, perception